2021
DOI: 10.1163/22134808-bja10061
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Information Facilitates the Categorization of Untrained Stimuli

Abstract: Although it has been demonstrated that multisensory information can facilitate object recognition and object memory, it remains unclear whether such facilitation effect exists in category learning. To address this issue, comparable car images and sounds were first selected by a discrimination task in Experiment 1. Then, those selected images and sounds were utilized in a prototype category learning task in Experiments 2 and 3, in which participants were trained with auditory, visual, and audiovisual stimuli, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Therefore, in terms of perception, a multisensory environment is beneficial for detection and discrimination (Evans 2020;Marchant et al 2012;von Saldern and Noppeney 2013). Furthermore, in terms of higher cognitive processing, multisensory information can facilitate memory, decision-making, and learning (Eördegh et al 2019;Matusz et al 2017;Raposo et al 2012;Wu et al 2021). Thus, one may assume that the cue modality can influence the performance in probabilistic category learning and, further, the recruitment of different learning systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in terms of perception, a multisensory environment is beneficial for detection and discrimination (Evans 2020;Marchant et al 2012;von Saldern and Noppeney 2013). Furthermore, in terms of higher cognitive processing, multisensory information can facilitate memory, decision-making, and learning (Eördegh et al 2019;Matusz et al 2017;Raposo et al 2012;Wu et al 2021). Thus, one may assume that the cue modality can influence the performance in probabilistic category learning and, further, the recruitment of different learning systems.…”
Section: Introductionmentioning
confidence: 99%
“…As for the performance of different modalities, there have been inconsistent findings in previous research. On the one hand, category learning and associative learning literature suggest that cross-modality often has advantages over unimodality when crossmodal information is redundant (e.g., Wu et al 2021) or the when learning from stimuli in different modalities is conducted separately (Eördegh et al 2019). On the other hand, the detection task has shown that, when stimuli of different modalities are presented rapidly, participants often respond more to the visual component than the auditory component, known as the Colavita visual dominance effect (e.g., Colavita and Weisberg 1979;Koppen et al 2009).…”
Section: Introductionmentioning
confidence: 99%